Select the product of (-6x7y)(x3y5)

(-6x^7y)(x^3y^5) = -6x^7*x^3*y^5*y = -6x^10y^6

Question

Asked 11/23/2014 2:03:06 PM

Updated 11/24/2014 6:08:25 AM

1 Answer/Comment

s

Rating

8

(-6x^7y)(x^3y^5)

= -6x^7*x^3*y^5*y

= -6x^10y^6

= -6x^7*x^3*y^5*y

= -6x^10y^6

Added 11/24/2014 6:08:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/28/2014 1:57:22 AM], Rated good by andrewpallarca

Select the difference of (8x2 - 3x3) - (2x2 - 5x3).
8x6
8x5
6x2 - 8x3
6x2 + 2x3

Question

Updated 11/22/2014 6:44:41 PM

1 Answer/Comment

what is the difference of (8x2 - 3x3) - (2x2 - 5x3).
8x6
8x5
6x2 - 8x3
6x2 + 2x3

Question

Updated 11/17/2014 3:30:38 PM

1 Answer/Comment

Select the difference of (8x^2 - 3x^3) - (2x^2 - 5x^3) **Weegy:** (2x^2 - 3x^3) - (8x^2 - 5x^3)
= (2x^2 - 3x^3) + (-8x^2 + 5x^3)
= 2x^3 - 6x^2 **User:** Simplify the following expression. 2(8x + 2) **Weegy:** 2(8x + 2) = (2)(8x) + (2)(2) = 16x + 4 **User:** Select the product of (5x - 4)(5x + 9). (More)

Question

Updated 11/20/2014 1:01:14 PM

3 Answers/Comments

(5x - 4)(5x + 9)

= 5x*5x - 4*5x + 5x*9 - 4*9

= 25x^2 - 20x + 45x - 36

= 25x^2 + 25x - 36

= 5x*5x - 4*5x + 5x*9 - 4*9

= 25x^2 - 20x + 45x - 36

= 25x^2 + 25x - 36

Added 11/20/2014 5:42:20 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/20/2014 8:52:32 AM], Rated good by andrewpallarca

-7w^3 + 6w^2 - 9w - 21w^2 + 18w - 27 **Weegy:** -7w^3 + 6w^2 - 9w - 21w^2 + 18w-27
= (-7w^3) + (6w^2 + -21w^2) + (-9w + 18w) + (-27)
= -7w^3 - 15w^2 + 9w - 27 (More)

Question

Expert Answered

Updated 11/28/2014 1:56:52 AM

0 Answers/Comments

34,469,324

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 842 [Total 6715] Ratings 19 Comments 652 Invitations 0 Offline

There are no comments.